Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
câu a bằng 15/8
câu b bằng 19/6
câu c bằng 3/10
câu d bằng 27/4
2/3 + 3/4=17/12
9/4 + 3/5=57/20
5/24 + 1/4=11/24
3/15 - 5/35=2/35 18/27 - 2/6=1/3 37/12 - 3=1/12
11/9 x 3/22=1/6 7/13 x 13/7=1 4 x6/7=24/7
2/5 : 3/10=4/3 3/8 : 9/4=1/6 8/21 : 4/7=2/3
A =\(\frac{2}{5}\times\frac{4}{7}+\frac{3}{5}\times\frac{4}{7}\) B = \(\frac{17}{13}\times\frac{12}{17}-\frac{4}{13}\times\frac{12}{17}\) C = \(\frac{9}{14}:\frac{6}{7}+\frac{5}{14}:\frac{6}{7}\) D =\(\frac{9}{12}:\frac{7}{9}\times\frac{12}{19}\)
= \(\frac{4}{7}\times\left(\frac{2}{5}+\frac{3}{5}\right)\) =\(\left(\frac{17}{13}-\frac{4}{13}\right)\times\frac{12}{17}\) = \((\frac{9}{14}+\frac{5}{14}):\frac{6}{7}\) = \(\frac{9}{12}\times\frac{9}{7}\times\frac{12}{19}\)
=\(\frac{4}{7}\times1\) = \(1\times\frac{12}{17}\) = \(1:\frac{6}{7}\) = \(\frac{9\times9\times12}{12\times7\times19}\)
=\(\frac{4}{7}\) = \(\frac{12}{17}\) =\(\frac{7}{6}\) = \(\frac{9\times9}{7\times19}=\frac{81}{133}\)
a. \(\left(2-\frac{2}{17}\right)\times\frac{51}{64}\)
\(=\frac{22}{17}\times\frac{51}{64}\)
\(=\frac{22\times51}{17\times64}=\frac{1122}{1088}=\frac{561}{544}\)
b. \(\left(\frac{2}{5}+\frac{5}{7}\right)\times\frac{5}{13}\)
\(=\frac{39}{35}\times\frac{5}{13}\)
\(=\frac{3}{7}\)
c. \(\frac{13}{18}\div\left(\frac{7}{12}-\frac{4}{9}\right)\)
\(=\frac{13}{18}\div\frac{28}{27}\)
\(=\frac{13}{18}\times\frac{27}{28}=\frac{39}{56}\)
#z
\(\left(2-\frac{2}{17}\right)\times\frac{51}{64}\)
\(=\frac{32}{17}\times\frac{51}{64}\)
\(=\frac{1632}{1088}=\frac{3}{2}\)
\(\left(\frac{2}{5}+\frac{5}{7}\right)\times\frac{5}{13}\)
\(=\left(\frac{14}{35}+\frac{25}{35}\right)\times\frac{5}{13}\)
\(=\frac{39}{35}\times\frac{5}{13}\)
\(=\frac{195}{455}=\frac{3}{7}\)
\(\frac{13}{18}:\left(\frac{7}{12}-\frac{4}{9}\right)\)
\(=\frac{13}{18}:\left(\frac{63}{108}-\frac{48}{108}\right)\)
\(=\frac{13}{18}:\frac{5}{36}\)
\(=\frac{13}{18}\times\frac{36}{5}\)
\(=\frac{468}{90}=\frac{26}{5}\)
Bài giải
a, \(\frac{4}{5}-\frac{2}{3}+\frac{1}{5}-\frac{1}{3}\)
\(=\left(\frac{4}{5}+\frac{1}{5}\right)-\left(\frac{2}{3}+\frac{1}{3}\right)=1-1=0\)
b, \(\frac{2}{5}\text{ x }\frac{7}{4}-\frac{2}{5}\text{ x }\frac{3}{7}\)
\(=\frac{2}{5}\text{ x }\left(\frac{7}{4}-\frac{3}{7}\right)=\frac{2}{5}\text{ x }\frac{37}{28}=\frac{37}{70}\)
c, \(\frac{13}{4}\text{ x }\frac{2}{3}\text{ x }\frac{4}{13}\text{ x }\frac{3}{12}=\frac{13\text{ x }2\text{ x }4\text{ x }3}{4\text{ x }3\text{ x }13\text{ x }12}=\frac{1}{6}\)
d, \(\frac{75}{100}+\frac{18}{21}+\frac{19}{32}+\frac{1}{4}+\frac{3}{21}+\frac{13}{32}\)
\(=\frac{3}{4}+\frac{18}{21}+\frac{19}{32}+\frac{1}{4}+\frac{3}{21}+\frac{13}{32}\)
\(=\left(\frac{3}{4}+\frac{1}{4}\right)+\left(\frac{18}{21}+\frac{3}{21}\right)+\left(\frac{19}{32}+\frac{13}{32}\right)\)
\(=1+1+1\)
\(=3\)
e, \(\frac{2}{5}+\frac{6}{9}+\frac{3}{4}+\frac{3}{5}+\frac{1}{3}+\frac{1}{4}\)
\(=\frac{2}{5}+\frac{2}{3}+\frac{3}{4}+\frac{3}{5}+\frac{1}{3}+\frac{1}{4}\)
\(=\frac{1}{5}\left(2+3\right)+\frac{1}{3}\left(2+1\right)+\frac{1}{4}\left(3+1\right)\)
\(=\frac{1}{5}\cdot5+\frac{1}{3}\cdot3+\frac{1}{4}\cdot4\)
\(=1+1+1\)
\(=3\)
a, \(\frac{4}{5}-\frac{2}{3}+\frac{1}{5}-\frac{1}{3}\)
\(=\left(\frac{4}{5}+\frac{1}{5}\right)-\left(\frac{2}{3}+\frac{1}{3}\right)=1-1=0\)
b, \(\frac{2}{5}\text{ x }\frac{7}{4}-\frac{2}{5}\text{ x }\frac{3}{7}\)
\(=\frac{2}{5}\text{ x }\left(\frac{7}{4}-\frac{3}{7}\right)=\frac{2}{5}\text{ x }\frac{37}{28}=\frac{37}{70}\)
c, \(\frac{13}{4}\text{ x }\frac{2}{3}\text{ x }\frac{4}{13}\text{ x }\frac{3}{12}=\frac{13\text{ x }2\text{ x }4\text{ x }3}{4\text{ x }3\text{ x }13\text{ x }12}=\frac{1}{6}\)
d, \(\frac{75}{100}+\frac{18}{21}+\frac{19}{32}+\frac{1}{4}+\frac{3}{21}+\frac{13}{32}\)
\(=\frac{3}{4}+\frac{18}{21}+\frac{19}{32}+\frac{1}{4}+\frac{3}{21}+\frac{13}{32}\)
\(=\left(\frac{3}{4}+\frac{1}{4}\right)+\left(\frac{18}{21}+\frac{3}{21}\right)+\left(\frac{19}{32}+\frac{13}{32}\right)\)
\(=1+1+1\)
\(=3\)
e, \(\frac{2}{5}+\frac{6}{9}+\frac{3}{4}+\frac{3}{5}+\frac{1}{3}+\frac{1}{4}\)
\(=\frac{2}{5}+\frac{2}{3}+\frac{3}{4}+\frac{3}{5}+\frac{1}{3}+\frac{1}{4}\)
\(=\frac{1}{5}\left(2+3\right)+\frac{1}{3}\left(2+1\right)+\frac{1}{4}\left(3+1\right)\)
\(=\frac{1}{5}\cdot5+\frac{1}{3}\cdot3+\frac{1}{4}\cdot4\)
\(=1+1+1\)
\(=3\)
a: =11/4+5/4-9/8
=4-9/8=32/8-9/8=23/8
b: \(=\dfrac{6}{7}\cdot\dfrac{7}{4}+\dfrac{5}{3}=\dfrac{3}{2}+\dfrac{5}{3}=\dfrac{9+10}{6}=\dfrac{19}{6}\)
c: \(=\dfrac{13}{18}\cdot\dfrac{9}{5}-1=\dfrac{13}{10}-1=\dfrac{3}{10}\)
d: \(=3+\dfrac{9}{4}\cdot\dfrac{5}{3}=3+\dfrac{45}{12}=\dfrac{81}{12}=\dfrac{27}{4}\)
3/4+5/12=7/6
13/18-4/9=7/6
5/9-5/12=35/36
\(\frac{3}{4}\)+ \(\frac{5}{12}\)= \(\frac{9}{12}\)+ \(\frac{5}{12}\)= \(\frac{14}{12}\)= \(\frac{7}{6}\)
\(\frac{13}{18}\) - \(\frac{4}{9}\)= \(\frac{13}{18}\)- \(\frac{8}{18}\)= \(\frac{5}{18}\)
\(\frac{5}{9}\)- \(\frac{5}{12}\)= \(\frac{60}{108}\)- \(\frac{45}{108}\)= \(\frac{15}{108}\)= \(\frac{5}{26}\)